Supply chain efficiency of geographical indication arabica coffee: Case study in Pasuruan - Perdana, Randhiki Gusti; Sucipto, Sucipto; Dania, Wike Agustin Prima; Tolle, Herman (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
Arabica coffee from Pasuruan is one of Indonesia's flagship commodities, demonstrating strong competitiveness in both domestic and international markets. However, farmers frequently face obstacles related to market information access, which hinders their ability to identify trading partners that offer optimal profits. This study aims to examine the structure and efficiency of the Arabica coffee supply chain in Pasuruan. A random sampling technique was employed, involving 44 coffee farmers, 10 collectors, 5 wholesalers, and 1 exporter. Supply chain performance was evaluated through product and information flow analysis. Supply chain efficiency was measured using the farmer's share metric, which reached 82%. The study found that the supply chain structure consists of farmers, collectors/processors, wholesalers, and exporters. The supply chain flow includes product, information, and financial movements. Farmers obtain price information mainly from wholesalers and collectors, while wholesalers and exporters base their pricing on international coffee market benchmarks. Based on the farmer's share approach, marketing channels II, III, and IV were identified as efficient. The findings suggest that enhancing farmers' access to market information, strengthening farmer cooperatives, and improving infrastructure can further increase supply chain efficiency and strengthen farmers' bargaining positions, providing valuable input for policymakers and stakeholders aiming to develop more sustainable and inclusive coffee value chains.